The Impact of Digital Marketing and Brand Articulation Capabilities on Marketing Performance of Small and Medium Enterprises: Case Study in West Lombok Province - suleman, Dede; Ety Nurhayaty; Lukman Hakim; Helmy Ivan Taruna; Nurzalinar Joesah; Yuliana Saridewi Kusumastuti; Resti Yulistria (Dinasti International Journal of Digital Business Management, 2024)
This research investigates the influence of Digital Marketing and Brand Articulation Capabilities on SME Marketing Performance in West Lombok Province, Indonesia. The research results show that Digital Marketing has a positive and significant impact on the Marketing Performance of SMEs, and Brand Articulation Ability also plays an important role in improving their performance. In addition, this research reveals that Brand Articulation Ability acts as a mediating variable in the relationship between Digital Marketing and Marketing Performance. These findings have important implications for SME owners and marketing practitioners, highlighting the importance of investing in effective Digital Marketing and developing Brand Articulation Capabilities. The integration of a good Digital Marketing strategy and the ability to convey a clear brand message can help SMEs achieve success in an increasingly digital and competitive business era.